Pengaruh Proporsi Daun Sawi Hijau (Brassica chinensis) dan Rumput Laut (Eucheuma cottonii) terhadap Karakteristik Nori - Sari, Rindy Violita; Priyanto, Gatot (Seminar Nasional Lahan Suboptimal, 2023)
Sari, R.V., & Priyanto, G. (2023). Effect of mustard green leaves (Brassica chinensis) and seaweed (Eucheuma cottonii) proportions on nori characteristics. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 392-404).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The high demand for nori has resulted in increased imports of nori from abroad due to the small amount of Porphyra sp. seaweed that grows in Indonesia, so an alternative ingredients for making nori is needed.  The objectives of the research were to analyze the effect of the proportion of mustard green leaves pulp (Brassica chinensis) and seaweed pulp (Eucheuma cottonii) on physical, chemical, and organoleptic characteristics of nori.  This research used a factorial completely randomized design with two treatment factors, namely seaweed pulp proportion (A1= 40 % (160 g seaweed / 400 mL water), A2= 60 % (240 g seaweed / 400 mL water), A3= 80 % (320 g seaweed / 400 mL water)) and mustard green leaves pulp proportion (B1= 0 % (0 g mustard green leaves / 0 mL water), B2= 20 % (40 g mustard green leaves / 200 mL water), B3= 40 % (80 g mustard green leaves / 200 mL water), B4= 60 % (80 g mustard green leaves / 200 mL water).  Observed parameters in this research include color (lightness, greenness, and yellowness), nori sheet hardness, chemical characteristics (moisture content, ash content), and organoleptics (color, flavor, and taste).  The results showed that the proportion of seaweed pulp had a significant effect on the moisture content, ash content, and nori sheet hardness of the nori.  The mustard green leaves pulp treatment has a significant effect on the color (lightness, greenness, and yellowness), ash content, and nori sheet hardness of the nori.  Based on the results of the analysis showed that, the average value of the moisture content was 8.15 %-10.88 %, the ash content was 11.60 %-14.15 %, the nori sheet hardness was 133.53 gf-165.00 gf, lightness was 37.41-40.60, greenness was -3.33-1.34, and the yellowness was 10.63- 17.82. The A2B4 treatment (60 % seaweed pulp proportion : 60 % mustard green leaves pulp proportion) was the best treatment for making nori based on sensory test value.